PERAN INFRASTRUKTUR TRANSPORTASI DALAM PENGEMBANGAN PROVINSI LAMPUNG - Rahayu Sulistyorini (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2021)
Abstract Transportation infrastructures have a very important role in encouraging the growth of a region and at the same time driving the growth of the community's economy in that region. This study aims to examine the influence of existing transportation infrastructure in Lampung Province, namely toll roads, executive terminal at Bakauheni Port, and Raden Inten II Airport, on the development of Lampung Province. The data used were obtained from a survey of traffic volume passing the toll road and interviews with a number of respondents at Bakauheni Seaport. The results obtained indicate that the longer the distance traveled, the greater the opportunity for travelers to use the toll road. As for goods transport, the choice to use the toll road is also influenced by the type of goods being transported. The combination of toll road transportation infrastructure and an executive terminal at Bakauheni Seaport also influences tourists to visit Lampung Province. Keywords: transportation infrastructure; toll roads; executive terminal; seaport; airport. Abstrak Prasarana transportasi mempunyai peran yang sangat penting dalam mendorong pertumbuhan suatu wilayah dan sekaligus pendorong tumbuhnya perekonomian masyarakat di wilayah tersebut. Studi ini bertujuan untuk mengkaji pengaruh infrastruktur transportasi yang ada di Provinsi Lampung, yaitu jalan tol, dermaga eksekutif di Pelabuhan Bakauheni, dan Bandara Raden Inten II, terhadap perkembangan Provinsi Lampung. Data yang digunakan diperoleh dari survei volume lalu lintas yang melalui jalan tol serta wawancara terhadap sejumlah responden di Pelabuhan Bakauheni. Hasil yang diperoleh menunjukkan bahwa semakin panjang jarak yang ditempuh, semakin besar peluang pelaku perjalanan untuk menggunakan jalan tol. Sedangkan untuk perjalanan barang, pilihan untuk menggunakan jalan tol juga dipengaruhi oleh jenis barang yang diangkut. Gabungan infrastruktur transportasi jalan tol dan dermaga eksekutif di Pelabuhan Bakauheni ikut memengaruhi wisata-wan untuk berkunjung ke Provinsi Lampung. Kata-kata kunci: infrastruktur transportasi; jalan tol; dermaga eksekutif; pelabuhan; bandara.